The Incidence of Anemia and Its Relationship With Nutritional Status (A Study on Female Students at SMA Negeri 3 Gorontalo) - Inayah, Alifya Isty; Otto, Suliyanti; Dungga, Elvie Febriani; Ibrahim, Sri Andriani; Ihsan, Maimun (Jambura Medical and Health Science Journal, 2024)
Introduction: The calibre of its human resources dramatically impacts the development of a nation. However, specific health concerns, such as malnutrition, specifically anemia, continue to impede the progress of women of reproductive age, particularly teenage girls, due to the increasing requirement for iron during puberty and menstruation. This study aims to explore the correlation between nutritional status and the prevalence of anemia in female students, specifically focusing on high school students.Method: This cross-sectional study examined the correlation between the nutritional status of female students in grade XI at SMA Negeri 3 Gorontalo from September to November 2023. Microtoise and digital scales will be employed to obtain the student's body mass index (BMI) values to evaluate their nutritional status. Anemia will be detected using a digital strip-test Hb measuring instrument, and purposive sampling will be used as the sampling technique. The Spearman rank analysis test will be used to determine the significance of the associative hypothesis.Results: The study primarily consisted of young women, with the majority being 15 years old (41.2%), possessing normal nutritional status (76.5%), and not experiencing anemia (66.7%). An intriguing correlation was discovered between nutritional status and anemia incidence among female students at SMA Negeri 3 Gorontalo (r=-0.364, p= 0.009).Conclusion: The prevalence of anemia among female students at SMA Negeri 3 Gorontalo is related to their nutritional status. It is recommended that healthcare professionals provide counselling and education on anemia, particularly for teenage girls. Keywords: Anemia, teenage girl, nutritional status.